If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k + 18 = 3k + -1 Reorder the terms: 18 + 4k = 3k + -1 Reorder the terms: 18 + 4k = -1 + 3k Solving 18 + 4k = -1 + 3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3k' to each side of the equation. 18 + 4k + -3k = -1 + 3k + -3k Combine like terms: 4k + -3k = 1k 18 + 1k = -1 + 3k + -3k Combine like terms: 3k + -3k = 0 18 + 1k = -1 + 0 18 + 1k = -1 Add '-18' to each side of the equation. 18 + -18 + 1k = -1 + -18 Combine like terms: 18 + -18 = 0 0 + 1k = -1 + -18 1k = -1 + -18 Combine like terms: -1 + -18 = -19 1k = -19 Divide each side by '1'. k = -19 Simplifying k = -19
| a^2-10k+30=0 | | 4(y-1)+3(y+2)=5(y-4) | | 4x-12=8x-16-4x | | 6m-m=.833(6m-10) | | 5x/2-4=2x-7/6 | | 14(t-2)+7t=(3t+3)-11 | | 2x^3-12x^2+23x-11=0 | | 5h-13=6h-16 | | 2q^2-3q=0 | | 12(3x+4)-5(2x+3)=6x-77 | | 4g-7=33 | | 6x^2-24x+23=0 | | 3p=15-2p | | 2q^2+3q=0 | | m^2-8mn+7n^2=0 | | 15-y+y=15 | | 4(1-p)=4p+4 | | 3x+1x=6 | | (8t+30)+(2t-16)=-22 | | x=15-y | | x+.67x=32.7 | | 10z-45=9z-45+z | | 2.5y+6=4.5y | | -2(3w-5)=10 | | 3a+8=5a-6 | | 6p-2p=5 | | 10x+6=2x | | 45+3x=-15 | | 3-4x+6-5y-20=0 | | x/7-2=-11 | | a+b=x | | (x^3)-27=0 |